Analisis soal HOTS pada Buku Studio Express A1 - Karim, Ella Mei Laila; Perdamean, Ahmad Sahat (IAI Nasional Laa Roiba Bogor, 2024)
The aim of this research is to find out how the questions are distributed in the Studio Express A1 book with the topic